EXPLORING CUSTOMERS’ EXPERIENCES OF ONLINE ORDERING AND DELIVERY SERVICES AT RESTO BUNGONG JAROE - Kultsum, Ummi (JURNAL ASIK, 2025)
The rapid growth of digital technology and the widespread adoption of online food ordering platforms have transformed consumer behavior and expectations in the restaurant industry. Customers now demand convenience, speed, and seamless service extending from order placement through delivery. This study explores the lived experiences of customers using the online ordering and delivery services at Resto Bungong Jaroe, aiming to understand factors influencing satisfaction and identify areas for service improvement. Using a qualitative research design, in-depth interviews were conducted with selected customers to gather rich, descriptive data about their perceptions, challenges, and emotional responses. Thematic analysis revealed key themes related to ease of ordering, delivery timeliness, accuracy, and communication quality. Findings indicate that while customers appreciate the convenience and accessibility of digital ordering, technical glitches and delivery delays remain significant pain points. Personalized communication and real-time tracking were identified as critical to enhancing satisfaction. The study concludes that harmoniousintegration of online interfaces with reliable delivery services is crucial for maintaining customer loyalty and competitive advantage.This research contributes to a deeper understanding of customer expectations in digital foodservice and offers practical insights for optimizing online ordering and delivery processes.